Talent Management in Music Organizations: Case Study of Jogja Acoustic Management - Vania Aristanisa; Ananta Dewi Rahayu; Rahmatulloh Rahmatulloh; Susilo Nugroho (TUMATA: Journal of Arts and Cultural Management, 2025)
Jogja Acoustic Management (JAM) is a community of musicians and street musicians established in 2020, which stands out among other street performers due to their appearance, musical ability, and complete music equipment spread across four points in Yogyakarta streets. This research aims to describe JAM’s business model through its talent management using a descriptive qualitative research method with a case study approach. This research complies with existing theory of Talent Management for outlining the pillars of talent management, which includes talent acquisition, activation, talent development, and talent retention. Data collection technique carried out by observation and semi-structured interviews. This research highlights how Jogja Acoustic Management (JAM), a street musician community in Yogyakarta, implements a grassroots model of talent management that aligns with the unique dynamics of informal arts organizations. With the absence of formal legal structure, JAM continuously improving their way to manage talent acquisition, activation, development, and retention through informal mechanisms rooted in community values and mutual support. Several suggestions for JAM are listed at conclusion. This research potentially serves as a model for other performing communities.